The Origin of the Gods : a Psychoanalytic Study of Greek Theogonic Myth. - Caldwell, Richard S. (Oxford University Press, 1993)
After describing those aspects of psychoanalytic theory that are relevant to the understanding of Greek myth, this study interprets, using psychoanalytical methodology, the Greek myth of origin and succession, particularly as stated in Hesiod's "Theogony."